Anti breast cancer properties and toxicity of Dillenia suffruticosa root aqueous extract in BALB/c mice - Saiful Yazan, Latifah; Yong, Sze Ong; Zaaba, Nur Elena; Mohd Ali, Razana; Jhi, Biau Foo; Yin, Sim Tor (Asian Pacific Journal of Tropical Biomedicine Editorial Office, 2015)
Objective To determine the anti-breast cancer activities and the safety oral consumption of Dillenia suffruticosa root aqueous extract (DRAE) in BALB/c mice.